Corowa-kun: A messenger app chatbot delivers COVID-19 vaccine information, Japan 2021. Issue 32 (30th July 2022) - Kobayashi, Takaaki; Nishina, Yuka; Tomoi, Hana; Harada, Ko; Tanaka, Kyuto; Matsumoto, Eiyu; Horimukai, Kenta; Ishihara, Jun; Sasaki, Shugo; Inaba, Kanako; Seguchi, Kyosuke; Takahashi, Hiromizu; et al.
Abstract: Background: There is a long history in Japan of public concerns about vaccine adverse events. Few studies have assessed how mobile messenger apps affect COVID-19 vaccine hesitancy. Methods: Corowa-kun, a free chatbot, was created on February 6, 2021 in LINE, the most popular messenger app in Japan. Corowa-kun provides instant, automated answers to 70 frequently asked COVID-19 vaccine questions. A cross-sectional survey with 21 questions was performed within Corowa-kun during April 5–12, 2021. Results: A total of 59, 676 persons used Corowa-kun during February–April 2021. Of them, 10, 192 users (17%) participated in the survey. Median age was 55 years (range 16–97), and most were female (74%). COVID-19 vaccine hesitancy reported by survey respondents decreased from 41% to 20% after using Corowa-kun. Of the 20% who remained hesitant, 16% (1, 675) were unsure, and 4% (3 6 4) did not intend to be vaccinated. Factors associated with vaccine hesitancy were: age 16–34 (odds ratio [OR] = 3.7; 95% confidential interval [CI]: 3.0–4.6, compared to age ≥ 65), female sex (OR = 2.4; Cl: 2.1–2.8), and history of a previous vaccine side-effect (OR = 2.5; Cl: 2.2–2.9). Being a physician (OR = 0.2; Cl: 0.1–0.4) and having received a flu vaccine the prior season (OR = 0.4; Cl: 0.3–0.4) were protective. Conclusions: A substantial number of people used the chabot in a short period. Mobile messenger apps could be leveraged to provide accurate vaccine information and to investigate vaccine intention and risk factors for vaccine hesitancy.